PENERAPAN TEKNIK KAIL UNTUK MENINGKATKAN PRESTASI BELAJAR PKn PADA SISWA KELAS VII B SMP NEGERI 1 PAYANGAN - Anom Separsa (Jurnal Santiaji Pendidikan (JSP), 2019)
This research aims to determine the improvement of learning achievement students of VII B SMP Negeri 1 Payangan with the application of the technique of KAIL (clarification of value).This research is a qualitative descriptive research with draft research action Model Kemmis.The subject of research is class VII B SMP Negeri 1 Payangan, amounting to 33 people.The learning performance Data of PKn is gathered with a study performance test of multiple choice and essay.Quantitative data analysis and data analysis techniques with comparisons of action I achievements with action II performance results.The results showed that the average value in the I cycle was 69 and the absorption rate was 69%, the average value of the II cycle was 83 and the absorbent power was 83%, an increase in learning performance by 14 points and an increase in its absorption power by 14%.The guidance of learning at cycle I amounted to 73% and in cycle II by 91%, there has been an increase in student learning by 18%.